Draft genome sequence of Pseudomonas extremaustralis strain USBA-GBX 515 isolated from Superparamo soil samples in Colombian Andes - Gina López; Carolina Diaz-Cárdenas; Nicole Shapiro; Tanja Woyke; Nikos C. Kyrpides; J. David Alzate; Laura N. González; Silvia Restrepo; Sandra Baena (Standards in Genomic Sciences, 2017)
Abstract Here we present the physiological features of Pseudomonas extremaustralis strain USBA-GBX-515 (CMPUJU 515), isolated from soils in Superparamo ecosystems, > 4000 m.a.s.l, in the northern Andes of South America, as well as the thorough analysis of the draft genome. Strain USBA-GBX-515 is a Gram-negative rod shaped bacterium of 1.0–3.0 μm × 0.5–1 μm, motile and unable to form spores, it grows aerobically and cells show one single flagellum. Several genetic indices, the phylogenetic analysis of the 16S rRNA gene sequence and the phenotypic characterization confirmed that USBA-GBX-515 is a member of Pseudomonas genus and, the similarity of the 16S rDNA sequence was 100% with P. extremaustralis strain CT14–3T. The draft genome of P. extremaustralis strain USBA-GBX-515 consisted of 6,143,638 Mb with a G + C content of 60.9 mol%. A total of 5665 genes were predicted and of those, 5544 were protein coding genes and 121 were RNA genes. The distribution of genes into COG functional categories showed that most genes were classified in the category of amino acid transport and metabolism (10.5%) followed by transcription (8.4%) and signal transduction mechanisms (7.3%). We performed experimental analyses of the lipolytic activity and results showed activity mainly on short chain fatty acids. The genome analysis demonstrated the existence of two genes, lip515A and est515A, related to a triacylglycerol lipase and carboxylesterase, respectively. Ammonification genes were also observed, mainly nitrate reductase genes. Genes related with synthesis of poly-hydroxyalkanoates (PHAs), especially poly-hydroxybutyrates (PHBs), were detected. The phaABC and phbABC operons also appeared complete in the genome. P. extremaustralis strain USBA-GBX-515 conserves the same gene organization of the type strain CT14–3T. We also thoroughly analyzed the potential for production of secondary metabolites finding close to 400 genes in 32 biosynthetic gene clusters involved in their production.